A rare case of a gastric adenomyoma mimicking a gastric duplication cyst - Arslan, Esra Elif; Acer Demir, Tuğba; Güney, Lütfi Hakan; Tepeoğlu, Merih; Sağnak Akıllı, Müge; Hiçsönmez, Akgün (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Arslan EE, Acer Demir T, Güney LH, Tepeoğlu M, Sağnak Akıllı M, Hiçsönmez A. A rare case of a gastric adenomyoma mimicking a gastric duplication cyst. Turk J Gastroenterol 2018; 29: 613-5.